Scope, Challenges and Prospects of Media Self-Regulation in Nepal - Pant, Laxman Datt; Nizam , Mohd Nashriq (NPRC Journal of Multidisciplinary Research, 2026)
Self-regulation is regarded as a crucial tool to maintain credibility and uphold media’s watchdog role in any democracy. It is one of the most effective ways to building trust among people about the content media produce. Both ethical standards and the practice of ombudsperson complement to enabling regulatory systems to promote self-regulation in newsrooms and safeguard editorial independence. Yet, practicing these principles remains problematic as Nepali media fraternity faces multiple challenges in developing systems of self-regulation. The current regulatory system at the Press Council Nepal (PCN) is less effective in facilitating self-regulation among journalists. The key obstacles of a functional self-regulation system include but not limited to financial crisis, government influence and intervention in PCN decisions, political alignment of the PCN board and media, and weak governance capacity to facilitate media I applying ethical codes voluntarily. Lack of sensitivity on ethical standards and non- adherence to journalists’ code of conduct are also complicated the situation. Absence of policy and plan to address growing ethical concerns across digital platforms i.e. online news portals has further intensified the problem. Digital newsrooms hardly have systems of transparent editorial gatekeeping. Identifying the scope of media self-regulation, this study analyzes the main obstacles in institutionalizing media self-regulation system. Furthermore, the study attempts to find out practical solutions of the problem and recommends contextual approaches to upholding media self-regulation in Nepal. Finding solutions to the crisis of the public trust over the media emerges as a major cornerstone of viable self-regulatory systems. It is recommended that initiatives should focus on developing an independent media regulatory body with mandates to facilitate self-regulation and sensitize media on contemporary ethical standards that advocate social responsibility of the press. Applying self-regulatory ethical standards is not a stand-alone task, it thrives when various stakeholders mainly journalists, publishers, the academia, regulatory bodies, civil society organizations come together to acknowledge the broader societal role of media. Addressing public grievances and reinforcing media self-regulation will create enabling environment to uphold media credibility and press freedom. Analyzing international studies and drawing on the observations of diverse media stakeholders, this study discusses the scope, challenges and prospects of self-regulation in Nepali media.